2014
DOI: 10.1017/s0029665114000196
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic activity of the gut microbiota and the impact of gluten free diet in children with coeliac disease

Abstract: The role of the gut microbiota in coeliac disease (CD) is unclear and evidence remains inconclusive (1,2) . This study investigated the metabolic activity of the gut microbiota in patients with long standing CD (LS), healthy siblings of CD patients (HS), newly diagnosed CD patients (ND) followed from diagnosis up to one year of gluten free diet (GFD) and healthy controls (HC).Faecal pH and faecal concentration of ammonia, short chain fatty acids (SCFA), branched chain fatty acids (BCFA), lactate (L and D la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…Conversely to the four earlier cited studies ( Di Cagno et al, 2009 , 2011 ; Makinder et al, 2014 ; Zafeiropoulou et al, 2020 ), Nistal et al (2012) showed that T-CD had the highest concentration of fecal SCFAs. More in-depth, this class of FAs was markedly affected by the higher levels of acetic, propionic, and butyric acids compared to HC under a gluten-containing diet.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Conversely to the four earlier cited studies ( Di Cagno et al, 2009 , 2011 ; Makinder et al, 2014 ; Zafeiropoulou et al, 2020 ), Nistal et al (2012) showed that T-CD had the highest concentration of fecal SCFAs. More in-depth, this class of FAs was markedly affected by the higher levels of acetic, propionic, and butyric acids compared to HC under a gluten-containing diet.…”
Section: Resultscontrasting
confidence: 90%
“…However, some fecal metabolites significantly characterized T-CD, such as a lower fecal concentration of ammonia (vs. HC and U-CD) and D-lactic acid (vs. U-CD) and a higher concentration L-lactic acid (vs. U-CD). Also, Makinder et al’s (2014) study, the concentration of total SCFA and branched-chain fatty acids (BCFAs) did not differ between T-CD and HS, whereas propionic, butyric, and valeric acids as well as iso -butyrate, iso -valeric, and iso -caproic were significantly lower in the same T-CD than HC. In T-CD, the authors also assessed a higher value of total sulfide than HC.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Especially in CD, SCFAs are of major interest due to their involvement in immunomodulatory functions such as the production of regulatory T-cells (19). Some studies also reported alterations in SCFA production in CD patients (20)(21)(22), even when on a long-term gluten-free diet (23). Other metabolites with altered amounts in CD are glutamine and tryptophan, which also impact the immune system (24,25).…”
Section: Introductionmentioning
confidence: 99%